ORIENTASI STRATEGI DALAM PENGUKURAN - Eka Zahra Solikahan; Ali Mohammad (University of Merdeka Malang, 2018)
This study generally aims to explain the measurement of strategy orientation in more depth. The qualitative approach was used in this study, by applying library research methods. The data used in the form of secondary data, the scientific article to the source of the data used was elektonik data originating from Google Scholar, Emerald Insights, Sciencedirect, and SAGE. The results for measuring orientation strategy appropriate for SMEs, that are customers, competitors, low cost orientation, entrepreneurship and innovation. But generally orientation strategy can be classified into three main elements, first market orientation, which consists of knowledge, competencies and skills of employees to build good relationships with consumers, second technology orientation which includes understanding employees and managers in the use of new technologies, and the last, Orientation to reduce the cost includes the tendency to reduce costs in the form of cost leadership strategies so that it can increase market share. Third this element can interact dynamically and continuously so that they will produce competitive advantages DOI : https://doi.org/10.26905/jbm.v5i2.2392